Competition law and economic regulation : making and managing markets - Dunne, Niamh, 1984- (Cambridge University Press, 2015)
"Niamh Dunne undertakes a systematic exploration of the relationship between competition law and economic regulation as legal mechanisms of market control. Beginning from a theoretical assessment of these legal instruments as discrete mechanisms, the author goes on to address numerous facets of the substantive interrelationship between competition law and economic regulation. She considers, amongst other aspects, the concept of regulatory competition law; deregulation, liberalisation and 'regulation for competition'; the concurrent application of competition law in regulated markets; and relevant institutional aspects including market study procedures, the distribution of enforcement powers between competition agencies and sector regulators, and certain legal powers that demonstrate a 'hybridised' quality lying between competition law and economic regulation. Throughout her assessment, Dunne identifies and explores recurrent considerations that inform and shape the optimal relationship between these legal mechanisms within any jurisdiction"--